Question #8c1e4

1 Answer
Feb 5, 2017

Answer:

#x=3# and #y=1#

Explanation:

#-3x+2y=-7#
#3x+3y=12#

From the first equation, derive a value for #3x#.

#-3x+2y=-7#

Multiply all terms with #-1#.

#3x-2y=7#

Add #2y# to both sides.

#3x=7+2y#

In the second equation, substitute #3x# with #color(red)((7+2y))#.

#3x+3y=12#

#color(red)((7+2y))+3y=12#

Open the brackets and simplify.

#color(red)(7+2y)+3y=12#

#7+5y=12#

Subtract #7# from each side.

#5y=5#

Divide both sides by #5#.

#y=1#

In the second equation, substitute #y# with #color(blue)(1)#.

#3x+3y=12#

#3x+3color(blue)((1))=12#

Open the brackets and simplify.

#3x+3=12#

Subtract #3# from each side.

#3x=9#

Divide both sides by #3#.

#x=3#